Pengaruh Harga, Promosi dan Kepercayaan Terhadap Keputusan Pembelian Online (Studi Kasus Pada Konsumen Lazada) - surliana surliana; Zulkarnaen Zulkarnaen; Irianto Irianto; Baiq Kisnawati (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
This research is aimed determining the effect of price, promotion, and trust on online purchasing decisions at Lazada site. This research is an associative study. Population used in this is all students of STIE AMM Mataram who had been shopping online at Lazada. The sampling technique used purposive sampling, in order to obtain a total sample of 40 people. Data analysis technique used is multiple regressions. The result of this research shows that: price effect and insignifican on online purchasing decisions, evidenced from t value obtained less than t table that is 0,262< 1,688. Promotion has a positive and significant effect on online purchasing decisions, evidenced from t value obtained greater than t table that is 2,674> 1,688. Trust has a positive and significant effect on online purchasing decisions, evidenced from t value obtained greater than t table that is 3,176>1,688. Price, promotion, and trust simultaneously has a positive and significan effect on online purchasing decisions,evidenced from t value obtained is 15,924.